2008
DOI: 10.1002/pssc.200779315
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of ZnO thin films grown on c‐Al2O3 by pulsed laser deposition in N2 + O2 ambient

Abstract: ZnO films were deposited on c‐Al2O3 using pulsed laser deposition both with and without N2 in the growth ambient. X‐ray diffraction revealed poorer crystal quality and surface morphology for one‐step growths with N2 in the ambient. A marked improvement in both the crystallographic and surface quality was obtained through use of two‐step growths employing nominally undoped ZnO buffer layers prior to growth with N2 in the ambient. All films showed majority n‐type conduction in Hall measurements. Post‐annealing f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The 270 nm thick ZnO layer was deposited by pulsed laser deposition method on c-Al 2 O 3 substrate in N 2 /O 2 atmosphere [9]. The electron beam written seed pattern for the growth was created by a JEOL JSM-IC848 scanning electron microscope in which the electron beam is controlled by Elphy Quantum 4.0 (Raith) system.…”
Section: Methodsmentioning
confidence: 99%
“…The 270 nm thick ZnO layer was deposited by pulsed laser deposition method on c-Al 2 O 3 substrate in N 2 /O 2 atmosphere [9]. The electron beam written seed pattern for the growth was created by a JEOL JSM-IC848 scanning electron microscope in which the electron beam is controlled by Elphy Quantum 4.0 (Raith) system.…”
Section: Methodsmentioning
confidence: 99%
“…Substrates of Si (111) and c‐plane sapphire (c‐Al 2 O 3 ) were used for the growth of the ZnO nanostructures. The samples were grown by PLD from a 99.99% pure ZnO target using a KrF excimer laser (248 nm) as described elsewhere 3–5. The sample morphology was studied using a Hitachi S4800 field emission‐SEM.…”
Section: Methodsmentioning
confidence: 99%
“…During the last decade, zinc oxide nanostructures have been extensively studied due to their potential relevance in optoelectronics, spintronics and bio‐applications 1. Pulsed laser deposition (PLD) is recognized as one of the most powerful techniques for the growth of ZnO‐based thin films and it has recently shown a tendency for the growth of self‐organizing ZnO‐based nanostructures arrays 1–3. In previous studies 4, it was found that self‐forming arrays of vertically aligned nanocolumns and nanocones can be grown by PLD under optimized growth conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The strains in the in-plane directions are considered to be generated from the anisotropic lattice matching and thermal contraction of the sapphire substrate. In order to prepare the substrate [110]. Novel Aurora PLD method was also developed by applying substrate temperature and enhance the photoluminescence [111,112].…”
Section: Growth Of Zno Thin Filmsmentioning
confidence: 99%